The Influence of Midwife Visits on the Choice of Long-Term Contraceptive Methods - Meliyanti Esa; Anik Sri Purwanti (Lembaga Pengembangan Kinerja Dosen, 2025)
Background: Women's choice of long-term contraceptive methods (LTCM) is influenced by factors such as counseling, knowledge, and healthcare access. Midwife visits play a key role in providing information and guidance on family planning, including LTCMs like implants, IUDs, and sterilization. Previous studies have shown that healthcare provider interaction enhances awareness and decision-making regarding contraception. However, many women still face barriers, including misinformation, fear of side effects, and cultural beliefs. Understanding how midwife visits shape contraceptive choices is essential for improving maternal and child health outcomes, reducing unintended pregnancies, and supporting family planning programs. Objective: This study aimed to analyze the impact of midwife visits on women’s choice of LTCMs in the reproductive age group. Methods: A quantitative, observational study with a cross-sectional design was conducted with 30 women who had received at least one midwife visit. Data were collected through structured interviews and family planning record reviews. The Wilcoxon signed-rank test examined the relationship between midwife visits and LTCM choices, with a significance level set at p < 0.05. Results: All participants received midwife visits. 20 (90%) chose LTCMs, while 10 (10%) opted for short-term methods. Statistical analysis revealed a significant relationship between midwife visits and LTCM choice (p = 0.000). Conclusion: Midwife visits significantly influence women’s choice of LTCMs, improving knowledge and decision-making. Strengthening midwife outreach can increase LTCM uptake and enhance family planning strategies.